2008
DOI: 10.1177/1066480708323198
|View full text |Cite
|
Sign up to set email alerts
|

Treating Infidelity: Considering Narratives of Attachment

Abstract: This article presents a counseling model for treating infidelity based on the integration of key aspects of attachment theory into a narrative therapy approach. The authors describe specific guidelines for their model after first reviewing personal attachment styles with a proclivity toward infidelity and providing a brief review of initial treatment considerations. Finally, they present a case example illustrating the use of narrative therapy and attachment theory as a model for treating infidelity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
3
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 20 publications
1
20
3
4
Order By: Relevance
“…Research by Mikulincer and Shaver (2007) showed that avoidant individuals hold themselves in high regard and therefore reason that through cheating they can share more of themselves with others. Duba, Kindsvatter, and Lara (2008) demonstrated that insecure-anxious individuals, who have a negative view of themselves, are more likely to cheat because they need high levels of attention, approval, and support from others. According to Platt, Nalbone, Casanova, and Wetchler (2008), parents who engage in infidelity are more likely to have children who also participate in extradyadic relationships.…”
Section: Study 2 Discussionmentioning
confidence: 99%
“…Research by Mikulincer and Shaver (2007) showed that avoidant individuals hold themselves in high regard and therefore reason that through cheating they can share more of themselves with others. Duba, Kindsvatter, and Lara (2008) demonstrated that insecure-anxious individuals, who have a negative view of themselves, are more likely to cheat because they need high levels of attention, approval, and support from others. According to Platt, Nalbone, Casanova, and Wetchler (2008), parents who engage in infidelity are more likely to have children who also participate in extradyadic relationships.…”
Section: Study 2 Discussionmentioning
confidence: 99%
“…O menor investimento, e consequente menor compromisso com o parceiro, poderão reduzir as barreiras ao envolvimento com terceiros. Além disso, o indivíduo evitante poderá utilizar a infidelidade como forma de reduzir o envolvimento emocional e aumentar o distanciamento em relação ao parceiro (Duba, Kindsvatter, & Lara, 2008).…”
Section: Revista Iberoamericana De Diagnóstico Y Evaluación -E Avaliaunclassified
“…However, in most cases, context was primarily understood as relationship factors along with aspects of individual functioning and family of origin issues: “…exploration of these undercurrents, these unseen foundations [multigenerational roots], will become one of the primary goals of the therapy” (Moultrup, 2005). Culture was also mentioned as a contextual component (i.e., Allen & Atkins, 2005; Duba, Kindsvatter, & Lara, 2008; Dupree et al., 2007) as well as social scripts (Parker, Berger, & Campbell, 2010), but suggestions for how to work with these issues were only included when personal or societal narratives were identified as a clinical focus, as in this example from Duba et al. (2008):…”
Section: (In)attention To Gender and Power Across Treatmentmentioning
confidence: 99%